Предмет: Алгебра,
автор: ира1062
быстро если можно ,очень надо
Приложения:
Ответы
Автор ответа:
1
a)x1,2=(-b(+-√d))/2a=(2(+-)4)/2*1=1+-2
x1=3
x2=-1
в)d=b^2-4ac=16+4*2*1=16+8=24
x1,2=(-b+-√d)/2a=(-4+-√24)/2*2=(-4+-2√6)/4=(-2+-√6)/2
x1=(-2-√6)/2
x2=(-2+√6)/2
x1=3
x2=-1
в)d=b^2-4ac=16+4*2*1=16+8=24
x1,2=(-b+-√d)/2a=(-4+-√24)/2*2=(-4+-2√6)/4=(-2+-√6)/2
x1=(-2-√6)/2
x2=(-2+√6)/2
Похожие вопросы
Предмет: Астрономия,
автор: kamkawwyy
Предмет: Алгебра,
автор: rufinaaaaaa44
Предмет: Биология,
автор: klittbay
Предмет: Математика,
автор: ZHEKA591
Предмет: Математика,
автор: yanashakleina20